PENGARUH DANA SERTIFIKASI DAN DANA ALOKASI KHUSUS TERHADAP HASIL BELAJAR SISWA (Survei Pada Sekolah Menengah Di Kota Palu) - Idawati, Idawati (Katalogis, 2017)
The study aims to determine and analyze simultaneous and partial impact of certification funds and specific allocation funds and student’s learning outcomes.Sample consists of 31 schools in Palu City that selected through purposive sampling method based on the researcher’s judgment. Method of analysis is quantitative and multiple linear regressions. The results find that one unit increase of certification funds and specific allocation funds will also increase student’s learning outcomes. The test shows that certification funds and specific allocation funds have simultaneously have impact on student’s learning outcomes in 31 schools in Palu. Partial test also shows that certification funds and specific allocation funds have significant impactson student’s learning outcomes in 31 junior middle schools in Palu City.Determinant coefficient of adjusted R-square of 0,293 indicates that 29,30 % of student’s learning outcomes is impacted by certification funds and specific allocation funds, while 70,70 % belongs to variables that are not studied.